IMPROVING FRONTLINER MERCHANDISER CAPABILITY THROUGH STANDARDIZED ONBOARDING: A CASE STUDY IN THE FMCG INDUSTRY - Aprilianto Setyawan; Aurik Gustomo (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
For sustainable business growth in the FMCG industry, consistently achieving KPI targets for frontliner merchandiser and salesman is a must because they are fully supported by marketing and the company to do that. Data shows that 54 merchandisers in eight areas of Jakarta only achieved 80.4% of their on-time Visibility KPI target in the third week of August 2025, which should have been achieved in every second week. The purpose of this study is to identify the causes of this gap, design a scalable and sustainable onboarding framework that can be applied across all regions and third-party agencies. The study used Focus Group Discussions, interviews, and fishbone analysis to understand what happens in actual field operations. After gathering feedback, validating the root causes of key issues, and training trends, especially for new employees entering the field without clear guidance, this study aims to find solutions and model recommendations. Based on these insights, the recommendation is to build a standardized onboarding framework and training materials through ADKAR approach that provide the same basic skills for every frontliner merchandiser. A structured and sustainable onboarding process is expected to improve capabilities, increase KPI-productivity achievement, and support long-term operational consistency.